Socially responsible investing as a tool for achieving sustainable development goals - Lipych, Liubov (Global Prosperity, 2025)
Abstract. The article explores the development of the concept of Corporate Social Responsibility (CSR) and Socially Responsible Investing (SRI) in the context of implementing European sustainability reporting standards. It is established that the modern business model is shifting from a profit-oriented approach to integrating environmental, social, and governance (ESG) factors into strategic planning. The paper reveals the essence of the EU regulatory framework for sustainable finance, particularly the provisions of the Sustainable Finance Disclosure Regulation (SFDR), Regulatory Technical Standards (RTS), the Non-Financial Reporting Directive (NFRD), and the new Corporate Sustainability Reporting Directive (CSRD), which require companies to disclose non-financial information. The study emphasizes the role of socially responsible investing as a key mechanism for achieving the Sustainable Development Goals (SDGs), combining financial efficiency with ecological and social effectiveness. It is shown that ESG-based approaches help minimize reputational, environmental, and social risks while increasing enterprises’ attractiveness to international investors. Special attention is paid to current trends in implementing sustainability principles in Ukraine. It is noted that Ukrainian companies are at the initial stage of ESG integration, though interest in it is growing under the influence of European requirements and investor expectations. The key elements of the Strategy for the Implementation of Sustainability Reporting (approved by the Government of Ukraine in 2024) and the Draft Law of Ukraine (2025) amending the Law "On Accounting and Financial Reporting in Ukraine" to introduce ESRS standards are outlined. It is argued that the establishment of a national non-financial reporting system is a prerequisite for increasing business transparency, investor confidence, and harmonizing the Ukrainian capital market with the European one. The study concludes that socially responsible investing in Ukraine should become a strategic mechanism for post-war recovery, contributing to the formation of an inclusive, human- and environment-oriented economy. This requires improving the regulatory framework, strengthening the institutional capacity of financial institutions, developing public-private partnership mechanisms, and establishing a system of independent sustainability reporting audits.